NON-STATIONARY HE-WEAK STAR HD182255? - Glagolevskij, Yu. V.; Shavrina, A. V.; Chuntonov, G. A. (Одеські астрономічні публікації, 2010)
It is known that the chemical elements distribution on the surface of chemically peculiar (CP) stars are associated with the distribution of the magnetic field. It is interest to study CP stars of various types and temperatures for the distribution of chemical elements on the surface. To this aim our research program includes HgMn star HD 182255 with no magnetic field, but with spectral and photometric variability, which is unusual in terms of the aforementioned. We suspect that the non-uniform distribution of helium and silicon on the surface of the star is due to the influence of the weak magnetic field.